Field trip to Niagara Falls - Stilton, Geronimo; Keys, Larry; Rattonchi, Rattero; Sacchi, Chiara; Piemme, Edizioni (New York Scholastic Inc., 2005)
Geronimo Stilton recounts his trip to Niagara Falls when he accompanies some young mice there as part of a school field trip
Keywords: Stilton, Geronimo -- Juvenile fiction; Mice -- Juvenile fiction; School field trips -- Juvenile fiction; Niagara Falls (New York and Ontario) -- Juvenile fiction